The Effects of Cortical Reorganization and Applications of Functional Near-Infrared Spectroscopy in Deaf People and Cochlear Implant Users - Xiaoqing Zhou; Menglong Feng; Yaqin Hu; Chanyuan Zhang; Qingling Zhang; Xiaoqin Luo; Wei Yuan (Brain Sciences, 2022)
A cochlear implant (CI) is currently the only FDA-approved biomedical device that can restore hearing for the majority of patients with severe-to-profound sensorineural hearing loss (SNHL). While prelingually and postlingually deaf individuals benefit substantially from CI, the outcomes after implantation vary greatly. Numerous studies have attempted to study the variables that affect CI outcomes, including the personal characteristics of CI candidates, environmental variables, and device-related variables. Up to 80% of the results remained unexplainable because all these variables could only roughly predict auditory performance with a CI. Brain structure/function differences after hearing deprivation, that is, cortical reorganization, has gradually attracted the attention of neuroscientists. The cross-modal reorganization in the auditory cortex following deafness is thought to be a key factor in the success of CI. In recent years, the adaptive and maladaptive effects of this reorganization on CI rehabilitation have been argued because the neural mechanisms of how this reorganization impacts CI learning and rehabilitation have not been revealed. Due to the lack of brain processes describing how this plasticity affects CI learning and rehabilitation, the adaptive and deleterious consequences of this reorganization on CI outcomes have recently been the subject of debate. This review describes the evidence for different roles of cross-modal reorganization in CI performance and attempts to explore the possible reasons. Additionally, understanding the core influencing mechanism requires taking into account the cortical changes from deafness to hearing restoration. However, methodological issues have restricted longitudinal research on cortical function in CI. Functional near-infrared spectroscopy (fNIRS) has been increasingly used for the study of brain function and language assessment in CI because of its unique advantages, which are considered to have great potential. Here, we review studies on auditory cortex reorganization in deaf patients and CI recipients, and then we try to illustrate the feasibility of fNIRS as a neuroimaging tool in predicting and assessing speech performance in CI recipients. Here, we review research on the cross-modal reorganization of the auditory cortex in deaf patients and CI recipients and seek to demonstrate the viability of using fNIRS as a neuroimaging technique to predict and evaluate speech function in CI recipients.